Effect of partial Mo substitution by W on HDS activity using sulfide CoMoW/Al2O3–TiO2 catalysts. (1st December 2018) - Obeso-Estrella, R.; Fierro, J.L.G.; de León, J.N. Díaz; Fuentes, S.; Alonso-Nuñez, G.; Lugo-Medina, E.; Pawelec, B.; Zepeda, T.A.
Graphical abstract: Highlights: Partial substitution of Mo by W in the CoMo/Al2 O3 –TiO2 catalyst leads to enhance of the catalyst metal and acid functions. The W–rich CoMoW catalyst exhibited higher specific activity than CoMo. Abstract: A series of Al2 O3 –TiO2 -supported trimetallic CoMoW catalysts were prepared with the aim to study the effect of Mo substitution by W on the catalyst performance in deep hydrodesulfurization (HDS) reaction. The oxide catalyst precursors were characterized by N2 physisorption, temperature-programmed desorption of NH3 (TPD-NH3 ), temperature-programmed reduction (TPR), diffuse reflectance spectroscopy (DRS UV–vis) and Raman spectroscopy. Sulfided catalysts were characterized by X-ray photoelectron spectroscopy (XPS) and high resolution transmission electron microscopy (HRTEM), and tested in the dibenzothiophene (DBT) hydrodesulfurization (HDS) reaction carried out in a batch reactor at T = 320 °C and total H2 pressure of 5.5 MPa. It was found that partial substitution of Mo by W leads to enhancement of catalyst metal and acid functions. The W-rich catalyst (W/Mo atomic ratio of 1.2) exhibited the best catalytic behavior and a larger selectivity toward HYD route products than W-free CoMo counterpart. The catalyst structure-activity correlation suggested that this is due to the combined effects of the best dispersion of metal oxides, the enhance of the catalyst acidity, a lower stacking of Mo(W)S2 layers and the formation of mixed "Co–Mo(W)–S" phase. In contrast, the less active phase (CoMo2 S4 ) was formed on the surface of the conventional CoMo catalyst. For all catalysts, The HDS reaction proceeds via direct desulfurization (DDS) and hydrogenation (HYD) reaction routes, the former being the main reaction route.